The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1590/s0006-87052001000300007
|View full text |Cite
|
Sign up to set email alerts
|

Banco De Sementes De Plantas Daninhas Em Solo Cultivado Com Adubos Verdes

Abstract: Com o objetivo de estudar a composição de banco de sementes de plantas daninhas em solo cultivado com adubos verdes, desenvolveu-se um experimento em casa de vegetação do Departamento de Produção Vegetal da Escola Superior de Agricultura "Luiz de Queiroz" (ESALQ/USP), Piracicaba (SP), entre dezembro de 1999 e fevereiro de 2000. As parcelas experimentais, compostas de 1 kg de solo amostrado por um trado de 4,3 cm de diâmetro, a partir da experimentação em campo, foram instaladas em bandejas de 30 x 20 x 5 cm. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
0
7
0
5
Order By: Relevance
“…Particularly for leguminous plants, nitrogen fixing may be severely affected by Al toxicity in subsoil (Silva and Sodek, 1997). These consequences, taken together, may decrease carbon sequestration and biomass formation, which is the key for nutrient recycling in soil (Alcântara et al, 2000), physical protection of soil against high temperatures (Oliveira et al, 2002) and erosion (Nascimento and Lombardi Neto, 1999), weed control (Severino and Christoffoleti, 2001), nitrogen incorporation (Debarba and Amado, 1997) and addition of organic carbon to soil (Testa et al, 1992). Recently there has been great interest in tropical leguminous plants, because of the increased adoption of green manuring in Brazilian cerrados (savannah) (Amado et al, 1999) and fruitproducing regions, for example in citrus orchards (Silva et al, 2002b) as a result of the necessity of a stable and sustainable production.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly for leguminous plants, nitrogen fixing may be severely affected by Al toxicity in subsoil (Silva and Sodek, 1997). These consequences, taken together, may decrease carbon sequestration and biomass formation, which is the key for nutrient recycling in soil (Alcântara et al, 2000), physical protection of soil against high temperatures (Oliveira et al, 2002) and erosion (Nascimento and Lombardi Neto, 1999), weed control (Severino and Christoffoleti, 2001), nitrogen incorporation (Debarba and Amado, 1997) and addition of organic carbon to soil (Testa et al, 1992). Recently there has been great interest in tropical leguminous plants, because of the increased adoption of green manuring in Brazilian cerrados (savannah) (Amado et al, 1999) and fruitproducing regions, for example in citrus orchards (Silva et al, 2002b) as a result of the necessity of a stable and sustainable production.…”
Section: Introductionmentioning
confidence: 99%
“…Already CAVA et al (2008) found that plants such as C. juncea, C. spectabilis, M. aterrima and M. pruriens have high competitive capacity by reducing the production of dry mass and number of weeds. SEVERINO and CHRISTOFFOLETI (2001) found that the use of green manures Arachis pintoi, C. juncea and Cajanus cajan have significantly reduced the seed bank of species Brachiaria decumbens, Panicum maximum and Bidens pilosa.…”
Section: Weed Control By Allelopathic Effectmentioning
confidence: 98%
“…Segundo Pitelli (1998), muitas vezes, as reservas não são suficientes para garantir a sobrevivência de plântulas no espaço percorrido dentro da cobertura morta, para ter acesso à luz e iniciar o processo fotossintético. A cobertura do solo pode atuar também como barreira física, impedindo a incidência de luz e a realização de fotossíntese por aquelas plântulas que conseguiram emergir do solo (Azania et al, 2002) e dificultando a emergência de várias espécies de plantas daninhas, devido ao sombreamento (Severino & Christoffoleti, 2001;Constantin & Oliveira Junior, 2005) e à consequente redução da amplitude térmica do solo (Severino & Christoffoleti, 2001). …”
Section: Introductionunclassified